Epidermolytic palmoplantar keratoderma due to keratin 9 gene mutation (Arg163Trp). - Caglayan, A.O.; Uksal, U.; Hennies, H.C (European Journal of Pediatric Dermatology, 2009)
Epidermolytic palmoplantar keratoderma (EPPK, MIM #144200) is an autosomal dominant inherited skin disorder generally due to mutations of KRT9 gene, which is expressed exclusively in the differentiating skin of the palms and soles, and characterized clinically by diffuse, yellow thickening of the skin of the palms and soles. We investigated a Turkish girl, who presented hyperkeratosis of palms and soles. No other body sites were affected. Oral mucosa, hair and nails were normal. No other family member was affected. We performed KRT9 gene analysis and confirmed the diagnosis of epidermolytic palmoplantar keratoderma for the first time in Turkey.